The Age Limitation of Witness in Marriage Reviewing from Maqashid Al-Syariah - Albani, Muhammad Syukri; Kurniadi, Dedi (Jurnal Daulat Hukum, 2023)
Additional information regarding the age limit of witnesses in marriage, which is mandatory to be 19 years old is a polemic and has consequences if a witness is carried out by a person who has not reached the age of 19 years, then the witness is invalid according to the Regulation of the Minister of Religion No. 11 of 2007. As for the formulation of the problem in The writing of this thesis is (1) How is Islamic law reviewing PMA No. 11 of 2007 regarding the age limit of witnesses in marriage (2 ) How is PMA No. 11 of 2007 concerning the age limit of witnesses in marriage in terms of Maqashid Al-Syariah. To get the answer to the problem formulation above, the library research method is used. The data collection method is document study and descriptive analysis is used. The results of the study show that first, in a review of Islamic law, the age limit for witnesses using the Baligh standard in Article 19 paragraph 2 PMA No. 11 of 2007, is not explicitly regulated in either the Qur'an or Hadith. So the rules applied in PMA No. 11 of 2007 regarding Baligh, aged at least 19 years, according to the author, is a result of ijtihad, namely by using several opinions from the Hambali and Safi'i scholars, by using the definitive age limit , which is the age requirement for marriage witnesses at least 19 years. The law of age has never been found in the classical fiqh literature. So the author concludes that this is the result of contemporary ijtihad, namely PMA No. 11 of 2007.